Optic coherence tomography measurement of choroidal and retinal thicknesses after uncomplicated YAG laser capsulotomy - Yuvacı,İsa (2015)
ABSTRACT Purpose: Optic coherence tomography (OCT) evaluation of the choroid, retina, and retinal nerve fiber layer after uncomplicated yttrium-aluminum-garnet (YAG) laser capsulotomy. Methods: OCT analysis of retinal and choroidal structures was performed in 28 eyes of 28 patients following routine examinations before and 24 h, 72 h, 2 weeks, 4 weeks, and 12 weeks after YAG laser capsulotomy. Data were analyzed using the SPSS software. Results: Data collected before YAG capsulotomy and at the above mentioned follow-up visits are summarized as follows. Mean central subfoveal choroidal thickness before YAG capsulotomy was 275.85 ± 74.78 µm; it was 278.46 ± 83.46 µm, 283.39 ± 82.84 µm, 280.00 ± 77.16 µm, 278.37 ± 76.95 µm, and 278.67 ± 76.20 µm after YAG capsulotomy, respectively. Central macular thickness was 272.14 ± 25.76 µm before YAG capsulotomy; it was 266.53 ± 26.47 µm, 269.14 ± 27.20 µm, 272.17 ± 26.97 µm, 270.91 ± 26.79 µm, and 273 ± 26.63 µm after YAG capsulotomy, respectively. Mean retinal nerve fiber layer thickness before YAG was 99.89 ± 7.61 µm; it was 98.50 ± 8.62 µm, 98.14 ± 8.69 µm, 99.60 ± 8.39 µm, 99.60 ± 8.39 µm, and 99.60 ± 8.35 µm after YAG capsulotomy, respectively. No observed change was statistically significant. No significant changes were observed with regard to mean intraocular pressure. Conclusions: After YAG laser capsulotomy, no statistically significant changes were found in choroidal, retinal, and optical nerve fiber layer thicknesses, although slight thickness changes in these structures were observed, particularly during the first days.